How does inflation in advanced economies affect emerging market bond yields? empirical evidence from two channels - Park, Donghyun; Tian, Shu (Mandaluyong City, Metro Manila Asian Development Bank, 2023)
This study uses multivariable smooth transition autoregressive–vector autoregressive (STAR–VAR), a novel model to explore how inflation in advanced economies affects emerging market bond yields.
Keywords: .Economics.